Flavonoids - From Biosynthesis to Human Health 2017
DOI: 10.5772/68095
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: Anticancer Properties

Abstract: Flavonoids are plant secondary metabolites. They are mainly classified into four major groups, such as flavanols, flavones, anthocyanidins, and isoflavonoids. Furthermore, they are divided into some subclasses. They are available in dietary foods and they cure various diseases. Certain plants and spices contain flavonoids, which have been commonly used for thousands of years in traditional medicine. Some of the flavonoids have been clinically used in many countries. Baicalein and its glycosides are one among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 39 publications
(40 reference statements)
0
33
0
Order By: Relevance
“…Remarkably, the antioxidant activity of flavonoids is closely associated with anticancer regulation [ 50 ]. Meanwhile, phytoflavonoids are not harmful to normal myeloid, peripheral blood, and epithelial cell lines [ 51 ]. In our research, we also find a strong correlation between total phenolics and flavonoids, antioxidant and cytotoxic capacities in the ethyl acetate extract ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the antioxidant activity of flavonoids is closely associated with anticancer regulation [ 50 ]. Meanwhile, phytoflavonoids are not harmful to normal myeloid, peripheral blood, and epithelial cell lines [ 51 ]. In our research, we also find a strong correlation between total phenolics and flavonoids, antioxidant and cytotoxic capacities in the ethyl acetate extract ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…33 From previous studies, flavonoids have been shown to induce cell cycle arrest in G2 and mobile phase of cell cycle, inhibited heat-shock protein, tyrosine kinase and Ras protein as well as downregulated oestrogen receptor-binding capacity. 34 As most pathogenesis of cancer involve genetic abnormalities that result in p53-mutated proteins, downregulation of these proteins by flavonoid intake also affect cancer growth. 34 Interestingly, other Mallotus species such as M. apelta was found to have a strong cytotoxic effect against cancer cells.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…34 As most pathogenesis of cancer involve genetic abnormalities that result in p53-mutated proteins, downregulation of these proteins by flavonoid intake also affect cancer growth. 34 Interestingly, other Mallotus species such as M. apelta was found to have a strong cytotoxic effect against cancer cells. Benzopyran, 6-[10-oxo-30(R)-hydroxybutyl]-5,7-dimethoxy-2,2-dimethyl-2H-1-benzopyran, that was present in the plant was cytotoxic against two human cancer cell lines, human hepatocellular carcinoma and rhabdosarcoma.…”
Section: Cytotoxic Activitymentioning
confidence: 99%
“…In a study Longchar and Prasad [47] reported that combination treatment with ascorbic acid plus cisplatin has better therapeutic efficacy against murine ascites DL in comparison to cisplatin alone treatment and simultaneously helps in the recovery in cisplatininduced hematological values and significant reduction in mutagenic and genotoxic effects [14]. It has been reported that rutin effectively ameliorates the alterations in the hematological parameters through its antioxidant nature [49] and the side-effects of synthetic drugs may be decreased due to flavonoid content in the combinational drugs [50]. Thus, it may be suggested that rutin plus cisplatin combination treatment while illustrating protective ability against cisplatin induced hematotoxicity has promising therapeutic efficacy against cancers in general and murine ascites Dalton's lymphoma in particular.…”
Section: Discussionmentioning
confidence: 99%